Оптимальные оценки параметров микросейсмического фона - Мостовой, В.С. (Видавничий дім "Академперіодика" НАН України, 2007)
The structural analysis and identification of the dynamic parameters of structures, whose spectral characteristics occupy the seismic and lower parts of acoustic spectral bands are the extremely important themes in models of the monitoring of such structures with the purpose of a prediction of essential changes in dynamic сharacteristics. From the point of view of geometric sizes, these objects are large man-made or natural geological objects. The method of dynamic identification provides an opportunity to investigate the behaviour of a structure by means of non-destructive tests, allows estimating „the health” of this structure and a possible requirement for more detailed monitoring. The article gives a methodology for the identification of main structural parameters, such as the main eigenfrequencies and the Q-factor of a structure on these frequencies.